B-site multi-element doped perovskite material and application thereof in proton ceramic electrolytic tank and fuel cell
By using the multi-element doped perovskite material BaCo0.8 (Zr1/6Ti1/6Zn1/6In1/6Cu1/6Mo1/6)0.2O3-δ (BCZTZICM) as the cathode material of proton ceramic fuel cell (PCFC), the problem of insufficient oxygen reduction reaction activity and high thermal expansion coefficient under medium and low temperature conditions is solved, and efficient oxygen reduction reaction and structural stability are achieved.
Patent Information
- Application Number
- CN202510038070.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-09
AI Technical Summary
The existing proton ceramic fuel cell (PCFC) cathode materials have insufficient catalytic activity of oxygen reduction reaction (ORR) under medium and low temperature conditions, and the thermal expansion coefficient of high-performance cathode materials is high, resulting in thermal-mechanical instability, limiting their commercial applications.
The multi-element doped perovskite material BaCo0.8 (Zr1/6Ti1/6Zn1/6In1/6Cu1/6Mo1/6)0.2O3-δ (BCZTZICM) was used as the air electrode material, and prepared by the sol-gel method to improve the hydration reaction activity and oxygen reduction activity of the material, while reducing its thermal expansion coefficient.
It improves the oxygen reduction reaction activity of PCFC cathode material, reduces the thermal expansion coefficient, enhances the structural stability and durability of the material, and improves the electrochemical performance of fuel cells.
Smart Images

Figure CN119890332A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a B-site multi-element doped perovskite material and application thereof in a proton ceramic electrolytic cell and a fuel cell, belonging to the technical field of new energy materials. Background Art
[0002] At present, due to the worsening global environmental and climate problems and the increasingly severe energy crisis, the development of clean green energy has become an important research goal. Traditional fossil energy will produce a large amount of pollutants during use, causing serious environmental problems. As an alternative, hydrogen energy currently still mainly relies on coal and natural gas reforming to produce hydrogen, which cannot achieve zero carbon emissions. The raw materials for hydrogen production by water electrolysis are water and electricity, both of which are renewable energy sources. The hydrogen production process does not produce carbon emissions, so it has received widespread attention from all over the world. Among them, solid oxide electrolysis cells have become an excellent choice for industrialization due to their extremely high energy conversion efficiency and low-cost electrodes of non-precious metals. However, at present, due to its extremely high operating temperature (800-1000℃), its large-scale industrial development is seriously hindered. Therefore, in order to improve the stability of the electrolysis cell and reduce the material cost, the medium and low temperature (400-700℃) operating temperature is its development trend. As the operating temperature decreases, the conductivity of the oxygen ion conductor electrolyte decays rapidly, and the superiority of the proton conductor becomes apparent. Compared with the oxygen ion conductor, the advantages of the proton conductor solid oxide electrolyzer are: protons have a smaller ion radius, so they have a smaller activation energy during the transmission process; as the temperature decreases, the number of proton migration increases; water is introduced at the air electrode, which will not dilute the hydrogen, reducing the cost of the subsequent hydrogen purification process, etc. However, the oxygen evolution reaction carried out at the air electrode is a typical four-electron migration process, and the reaction energy barrier of this process is much higher than the hydrogen evolution reaction of the two-electron migration carried out at the hydrogen electrode. In addition, since the water vapor of the proton conductor is introduced by the air electrode, the water vapor must first be adsorbed at the air electrode and complete the oxygen evolution reaction, so its reaction is more complicated. Therefore, the development of air electrode materials for proton ceramic electrolyzers (PCECs) is a breakthrough direction in electrolyzer research.
[0003] On this basis, PCEC air electrode has evolved from the early oxygen ion (O 2- )Electronics - ) mixed conductors have evolved to today's oxygen ion (O 2- ), proton (H +) and electron conduction capacity. However, the current mainstream PCEC cathode is still dominated by oxygen ion transport, and the proton transport capacity is not strong. According to current research, water vapor mainly forms proton defects by combining with oxygen vacancies in the air electrode, thereby completing the migration of protons in the air electrode. Therefore, optimizing the hydration capacity of the air electrode is an important means to increase the proton defect concentration and thus increase the electrolytic current density of the electrolytic cell.
[0004] In addition, fuel cells have attracted widespread attention due to their durability, environmental friendliness, high energy conversion rate and safety. Solid oxide fuel cells are considered to be extremely promising energy conversion devices that can achieve efficient conversion of chemical energy into electrical energy and solve the problem of energy utilization efficiency. Compared with traditional solid oxide fuel cells (SOFCs) that mainly rely on oxygen ion conduction, proton ceramic fuel cells (PCFCs) can operate at medium and low temperatures (500-650°C) due to the lower activation energy required for proton conduction, thus avoiding the high operating costs, difficult equipment sealing, poor durability and other problems caused by high temperatures. PCFC is an energy conversion device based on proton conduction to achieve power generation, which can achieve efficient power generation using renewable energy or industrial hydrocarbon fuel waste gas.
[0005] However, one of the technical difficulties of PCFC is the insufficient catalytic activity of the oxygen reduction reaction (ORR) of the cathode as the temperature decreases, and the high-performance cathode of the current high-performance PCFC is mainly Co-based materials, whose high thermal expansion coefficient leads to the thermo-mechanical instability between the electrode and the electrolyte, which is also the main bottleneck of PCFC commercialization. Therefore, the development of cathodes with high electrocatalytic activity and low thermal expansion coefficient is of great significance to PCFC.
[0006] In recent years, many researchers have developed a large number of high-performance cathodes for SOFC by exploring different element doping, co-doping, and even diversified doping. However, the intrinsic mechanism based on element co-doping or diversified doping is still controversial. Zhou et al. synthesized SrCo 0.8 Nb 0.2 O 3-δ , SrCo 0.8 Ta 0.2 O 3-δ , SrCo 0.8 Nb 0.1 Ta 0.1 O 3-δThrough experiments and theoretical calculations, the main reason for the improvement of solid oxide fuel cell (SOFC) cathode performance by co-doping was explored. The study proposed that co-doping helps to promote the uniform distribution of Co elements, reduce the aggregation of oxygen vacancies to achieve rapid reduction of oxygen ions, and also helps to reduce the activation energy of oxygen reduction reaction, making the material based on oxygen ion conductor electrolyte Gd at 500 ° C. 0.1 Ce 0.9 O 1.9 0.1Ωcm was obtained on a symmetrical cell of (GDC) 2 Area specific impedance (ASR). (Non-patent document 1)
[0007] Take La 0.7 Sr 0.3 (Co,Cr,Fe,Mn,Ni)O 3-δ is the electrode, La 0.8 Sr 0.2 Ga 0.8 Mg 0.2 O 3-δ The polarization impedance of the symmetrical battery with electrolyte is 0.126Ωcm -2 When used as an air electrode in a fuel cell, the maximum power density of a single cell at 900°C reached 550 mW cm -2 This fully proves the feasibility of using high entropy perovskite as SOFC air electrode (Non-patent Document 2). At the same time, the doping of multiple B-site elements regulates the entropy value of the material, thereby improving the stability of the material, but it also inevitably reduces the electrochemical activity of the SOFC air electrode material.
[0008] Non-patent literature 1: Wenhuai Li, Mengran Li, Wei Zhou, et al. High CationicDispersity Boosted Oxygen Reduction Reactivity in Multi-Element DopedPerovskites[J]. Advanced Functional Materials, 2022, 2210496. (10.1002 / adfm.202210496)
[0009] Non-patent document 2: J,Olszewska A,Falkenstein A,et al.An InnovativeApproach to Design SOFC Air Electrode Materials:High Entropy La 1-x Sr x(Co,Cr,Fe,Mn,Ni)O 3-δ (x=0,0.1,0.2,0.3)Perovskites Synthesized by the Sol-Gel Method[J]. Journal of Materials Chemistry A, 2020, 8, 24455. (10.1039 / D0TA06356H). Summary of the invention
[0010] The present invention provides a high-performance proton conductor solid oxide electrolytic cell air electrode material BCZTZICM and its preparation method and application, which can improve the hydration reaction activity and thus enhance the performance of the electrolytic cell. 0.8 (Zr 1 / 6 Ti 1 / 6 Zn 1 / 6 In 1 / 6 Cu 1 / 6 Mo 1 / 6 ) 0.2 O 3-δ The air electrode has excellent hydration reaction activity, excellent water vapor physical / chemical adsorption capacity, etc., which makes the air electrode material applicable to medium and low temperature proton conductor solid oxide electrolyzers; in addition, the material is applied to proton ceramic fuel cells PCFC, which can improve the oxygen reduction (ORR) activity of the cathode material and reduce its thermal expansion coefficient (TEC).
[0011] A proton conductor solid oxide material having a general composition formula of ABO 3-δ Perovskite oxide material with the molecular formula: BaCo x (Zr a Ti b Zn c In d Cu e Mo f ) y O 3-δ (BCZTZICM), where δ is the content of oxygen vacancies; and x+y=1 and a+b+c+d+e+f=1.
[0012] The molecular formula is: BaCo 0.8 (Zr 1 / 6 Ti 1 / 6 Zn 1 / 6 In 1 / 6 Cu 1 / 6 Mo 1 / 6 ) 0.2 O 3-δ .
[0013] The above-mentioned method for preparing the proton conductor solid oxide electrolytic cell air electrode material is to prepare it by a sol-gel method according to a stoichiometric ratio.
[0014] The sol-gel method comprises the following steps: firstly, tetrabutyl titanate and ammonium molybdate are heated with deionized water and monohydrated citric acid until they are clear and transparent, and then, they are prepared by the sol-gel method with barium nitrate, cobalt nitrate, zirconium nitrate, zinc nitrate, indium nitrate and copper nitrate according to the stoichiometric ratio in the molecular formula.
[0015] The method comprises the following steps: firstly, using deionized water and monohydrated citric acid to heat and dissolve tetrabutyl titanate and ammonium molybdate until they are clear and transparent, then adding barium nitrate, cobalt nitrate, zinc nitrate, zirconium nitrate, copper nitrate and indium nitrate to dissolve and heat and stir; adding ethylenediaminetetraacetic acid, then dripping ammonia water until the pH value of the solution is between 7 and 8, and volatilizing the water under the condition of heating and stirring to obtain a gel-like substance; placing the gel-like substance in an oven to dry to obtain an air electrode material precursor, and then placing the precursor in a muffle furnace to roast to obtain the required electrolytic cell air electrode material.
[0016] The total molar ratio of ethylenediaminetetraacetic acid and citric acid to Ba, Co, Zr, Ti, Zn, In, Cu, and Mo is 2:0.5-1.5:0.5-1.5.
[0017] The drying process is carried out at 160-200°C for 5-8 hours.
[0018] The calcination parameters are 1000°C for 1-10h.
[0019] The solid oxide material is used as a proton conductor in water electrolysis or in a fuel cell.
[0020] The electrolyte used is BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O3.
[0021] Anode materials include NiO and BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 A composite anode composed of O3(BZCYYb).
[0022] The mass ratio of NiO to electrolyte in the composite anode is (3-5):(6-7).
[0023] A method for characterizing the hydration reaction activity of an air electrode of a solid oxide electrolytic cell comprises the following steps:
[0024] The air electrode material powder with the same particle size is placed in a tube furnace and treated with dry air and wet air at the operating temperature and quenched as a characterization material;
[0025] Determine the ion valence of the characterization material and obtain the change in ion valence during dry air and wet air treatment;
[0026] It is judged that the material with a larger change has better hydration reaction activity.
[0027] The air electrode material powder is granulated to keep its particle size uniform.
[0028] The operating temperature is 500-700℃ for 1-5h.
[0029] The water vapor volume fraction of humid air is 1-40%.
[0030] The quenching method is air quenching, that is, the material is taken out and quickly cooled in the air.
[0031] The ion valence states were determined by X-ray absorption spectroscopy.
[0032] Beneficial Effects
[0033] Through the hydration reaction activity test, the valence state changes of variable valence ions of BCZTZICM, BCFZY and BSCF were 0.056, 0.049 and 0.043, respectively, indicating that BCZTZICM has stronger hydration reaction activity.
[0034] BaCo, a solid oxide electrolytic cell air electrode material prepared by sol-gel method 0.8 (Zr 1 / 6 Ti 1 / 6 Zn 1 / 6 In 1 / 6Cu 1 / 6 Mo 1 / 6 ) 0.2 O 3-δ (BCZTZICM). It has a high electrolytic current density. The electrolytic current density of the single cell prepared with Ni-BZCYYb as the anode support at 650℃, 600℃, 550℃, and 500℃ at 1.3V reaches 1.8Acm -2 , 1.4A cm -2 , 0.9Acm -2 , 0.6Acm -2 , which is higher than the 1.3 A cm obtained by BSCF and BCFZY at the corresponding temperature. -2 , 1.0Acm -2 , 0.7Acm -2 , 0.5A cm -2 .
[0035] The invention improves the ORR activity of PCFC cathode materials and reduces their thermal expansion coefficient. Zr, Ti, Zn, In, Cu and Mo are doped into conventional BaCoO in one step by a sol-gel method. 3-δ The B site is more easily regulated by the thermal expansion behavior of Co ions at the B site and the stretching vibration of the metal-oxygen bond between the B site element and the O element, thereby enhancing the ORR activity of the BCZTZICM cathode material in PCFC and reducing its thermal expansion coefficient to 17.67×10 -6 K -1 In addition, thanks to the reduction in the thermal expansion coefficient, the structural stability of the BCZTZICM cathode has been significantly improved, allowing the single cell to perform well in long-term stability tests.
[0036] As an excellent air electrode material, BCZTZICM has a peak power density of 1.3 W cm at 650 °C, 600 °C, 550 °C, and 500 °C in proton conductor fuel cell tests. -2 , 0.88W cm -2 , 0.68W cm -2 , 0.49W cm -2 . BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 is the selected area electron diffraction pattern of BCZTZICM;
[0038] Figure 2 ,a is the chemical compatibility test of BCZTZICM and BZCYYb electrolyte; b is the Rietveld refined XRD pattern of BCZTZICM material at room temperature;
[0039] Figure 3 This is a high-resolution transmission electron microscopy (HRTEM) image of BCZTZICM;
[0040] Figure 4 It is a BCZTZICM EDX-mapping image.
[0041] Figure 5 is the XRD pattern of BCZTZICM sample obtained at different temperatures;
[0042] Figure 6 It is the comparison of XRD patterns of BCZTZICM powder sample before and after calcination at 600℃ for 200 hours;
[0043] Figure 7 is the H2O-TPD diagram of BCZTZICM, BSCF and BCFZY;
[0044] Figure 8 It is the in-situ infrared spectra of water vapor adsorption of BCZTZICM, BSCF and BCFZY at 600℃;
[0045] Fig. 9 The X-ray near-edge structures of variable-valence ions of BCZTZICM, BSCF and BCFZY before and after passing water at 600°C and the valence state changes calculated from them;
[0046] Figure 9g It is the amount of valence change of variable-valence elements in a single sample;
[0047] Fig.10a It is an IV curve of an electrolytic cell (Ni-BZCYYb|BZCYYb|BCZTZICM) prepared with BCZTZICM as air electrode and Ni-BZCYYb as anode support tested in the range of 500-650°C;
[0048] Fig.10b and Fig.10c The IV curve of the electrolytic cell prepared with BSCF, BCFZY as air electrode and Ni-BZCYYb as anode support (Ni-BZCYYb|BZCYYb|BSCF / BCFZY) tested at 500-650℃.
[0049] Fig.11 This is a stability test diagram of the electrolytic cell with BCZTZICM as the air electrode.
[0050] Fig.12 It is the comparison of mass loss from room temperature to 1000℃ of BCZTZICM, BCFZY and BSCF;
[0051] Fig.13 It is the comparison of thermal expansion coefficients of BCZTZICM, BCFZY, BSCF and electrolyte BZCYYb;
[0052] Fig.14 are the XANES curves of BCZTZICM, BCFZY and BSCF at room temperature and 600°C and the valence state changes of variable valence ions calculated from the XANES curves;
[0053] Fig.15 This is the comparison of the O1s binding energy of XPS of BCZTZICM, BCFZY, and BSCF;
[0054] Fig.16 It is the Arrhenius plot of ASR obtained on symmetrical cells supported by BZCYYb for BCZTZICM, BCFZY, and BSCF under humid air conditions in the range of 500-700 °C;
[0055] Fig.17 It is the IVP curve of Ni-BZCYYb|BZCYYb|BCZTZICM single cell fuel cell in 500-650℃;
[0056] Fig.18 This is the stability test curve of the BCZTZICM single cell fuel cell at 550°C;
[0057] Fig.19 XRD phase structure comparison between single element doped samples and hexa-element doped BCZTZICM;
[0058] Fig. 20 XRD phase structure comparison of binary and quadruple-element doped samples and hexa-element doped BCZTZICM. DETAILED DESCRIPTION
[0059] The present invention provides a perovskite mixed conductor, the composition formula of which is ABO 3-δ , molecular formula: BaCo 0.8 (Zr 1 / 6 Ti 1 / 6 Zn 1 / 6 In 1 / 6 Cu 1 / 6 Mo 1 / 6 ) 0.2 O 3-δ (BCZTZICM), where δ represents the oxygen vacancy content.
[0060] The design concept of the above-mentioned perovskite mixed conductor is: BCZTZICM uses BaCoO 3-δ As a matrix material, it has excellent oxygen reduction activity, but its coplanar hexagonal phase structure weakens the charge and ion migration within the crystal. Here, we constructed BaCo by using trace doping of multiple elements at the B position. 0.8 (Zr 1 / 6 Ti 1 / 6 Zn 1 / 6 In 1 / 6 Cu 1 / 6Mo 1 / 6 ) 0.2 O 3-δ(BCZTZICM). The multi-element doping method transforms its structure into a cubic perovskite phase and the doping of multiple elements makes its oxygen vacancy distribution more uniform, thereby achieving excellent proton / oxygen ion migration activity, and the higher Co content also ensures its excellent electrocatalytic activity. Here, the oxygen ion / electron conductor BSCF with the same phase structure and excellent oxygen evolution reaction activity and the classic proton / oxygen ion / electron three-phase conductor BCFZY air electrode are studied as a comparison. The above materials can be prepared by the sol-gel method according to the composition ratio.
[0061] In addition to effectively increasing the entropy of the material, multi-element doping at the B site also reduces the thermal expansion coefficient of the material and improves the ORR activity and operating durability in the fuel cell. In the range of 300-800℃, BCZTZICM only shows 17.67×10 -6 K -1 The thermal expansion coefficient is much lower than 23-25×10 of BSCF and BCFZY -6 K -1 In single cell operation, the maximum peak power density of the BCZTZICM electrode at 650°C was 1.3 W cm -2 . The BCZTZICM electrode exhibits excellent durability in long-term operation of a single cell. This invention develops a high-performance proton ceramic fuel cell cathode material and preparation method, which greatly improves the electrochemical performance of proton conductor fuel cells.
[0062] In addition, the characterization of the hydration reaction ability of the air electrode of the proton conductor electrolytic cell is currently mainly focused on H2O-TPD and Karl Fischer water content titration, which cannot significantly characterize the progress of the hydration reaction and the generation of its intermediates. In order to characterize the hydration reaction ability of the above-mentioned materials, the present invention also provides a characterization test method. Mainly based on the following equation:
[0063]
[0064] in represents lattice oxygen, is an oxygen vacancy, It is a proton defect. Since proton defects will occupy oxygen sites and form bonds with surrounding metal ions, the content of proton defects can be obtained by detecting the change in the valence state of metal ions.
[0065] Example 1
[0066] This embodiment provides a proton conductor solid oxide electrolytic cell air electrode material BaCo 0.8 (Zr 1 / 6 Ti 1 / 6ZnIn 1 / 6Cu 1 / 6 Mo 1 / 6 ) 0.2 O 3-δ The preparation method comprises the following specific steps:
[0067] (1) Weigh 0.5729 g of tetrabutyl titanate, 0.2972 g of ammonium molybdate heptahydrate, and 42.028 g of citric acid monohydrate, and add an appropriate amount of deionized water to dissolve. Then add 13.1327 g of barium nitrate, 11.8185 g of cobalt nitrate, 0.7155 g of zirconium nitrate, 0.5008 g of zinc nitrate, 0.4067 g of copper nitrate, and 0.5014 g of indium nitrate. According to the molar ratio of ethylenediaminetetraacetic acid: monohydrate citric acid: metal ion = 1:2:1, weigh 29.224 g of ethylenediaminetetraacetic acid as a complexing agent and add an appropriate amount of deionized water.
[0068] (2) adding the obtained complexing agent to the dissolved metal ion solution, and then adding an appropriate amount of ammonia water to adjust the pH range of the solution to 7-8, and then heating and stirring until the water evaporates to obtain a colloidal substance.
[0069] (3) The colloidal substance is placed in an oven at 180° C. to remove moisture to obtain a precursor.
[0070] (4) The obtained precursor is placed in a muffle furnace and calcined for 5 hours at 1000°C to finally obtain the electrode powder.
[0071] Comparative experiment
[0072] BaCoO doped with one, two, and four B sites were prepared respectively. 3-δ The perovskite-based air electrode materials, the molecular formulas of which are mono-doped, are prepared in a similar manner to Example 1, except that no corresponding element is added to the metal salt of the sol-gel method. It can be seen from the XRD characterization data that these materials partially contain impurities, while the materials prepared in Example 1 do not contain impurities.
[0073] Example 2 In-situ test of chemical adsorption capacity of air electrode
[0074] (1) Weigh 0.03% of the air electrode powder BaCo prepared in Example 1. 0.8 (Zr 1 / 6 Ti 1 / 6 ZnIn 1 / 6 Cu 1 / 6Mo 1 / 6 ) 0.2 O 3-δ Mix well with 3g potassium bromide powder in a mortar, take 0.5g of it and add it to the high-temperature in-situ test bench, heat it to 600℃ at 10℃ / min, and dry it for 30min to eliminate the influence of air and adsorbed water in the sample on the test.
[0075] (2) The sample was dried and the initial state of the sample was compared with the standard sample using Fourier transform attenuated total reflection infrared spectroscopy. Then, air with water vapor was introduced and the 3200-3800cm -1 After 45 minutes of passing the water vapor, dry air was introduced and the intensity of the peak was measured at 3200-3800cm. -1 The intensity changes of the segment peaks were used to observe the removal of hydroxyl radicals.
[0076] Example 3 Preparation of electrolytic cell
[0077] (1) Weigh 0.35 g of NiO+BZCYYb uniformly mixed hydrogen electrode powder and press it into a green body at a pressure of 4 mPa.
[0078] (2) 1 g of BZCYYb powder was mixed with 20 ml of ethanol in a high-energy ball mill and ball-milled at 400 rpm for 1 h to obtain an electrolyte slurry, which was evenly sprayed on one side of the hydrogen electrode using a spraying device. When the single-piece spraying mass reached 0.015 g, the spraying was stopped and a tablet press was used to tightly bond the electrolyte of the semi-electrolytic cell green body to the hydrogen electrode, and then calcined at 1450°C for 5 h.
[0079] (3) Weigh 1 g of the cathode powder BaCo prepared in Example 1 0.8 (Zr 1 / 6 Ti 1 / 6 ZnIn 1 / 6 Cu 1 / 6 Mo 1 / 6 ) 0.2 O 3-δ , 10 ml of isopropanol, 2 ml of ethylene glycol, and 0.8 ml of propylene glycol were poured into a high-energy ball mill. After ball milling at 400 r / min for 30 min, the desired cathode slurry was obtained by transferring it to the culture bottle with a pipette.
[0080] (4) The prepared dry-pressed battery cell is placed on a heating table and preheated at 200°C. The prepared cathode slurry is evenly sprayed on the electrolyte surface of the dry-pressed cell using a spray gun under the push of inert gas. After the liquid evaporates completely, the sprayed dry-pressed battery is placed in a high-temperature muffle furnace and calcined at 900°C for 2 hours to obtain the required symmetrical battery, which is used for testing the electrolysis of water with cathode materials in the temperature range of 500-650°C.
[0081] Example 4
[0082] This embodiment provides a BaCo 0.8 (Zr 1 / 6 Ti 1 / 6 Zn 1 / 6 In 1 / 6 Cu1 / 6 Mo 1 / 6 ) 0.2 O 3-δ The preparation and testing method of the symmetrical battery of the electrode is as follows:
[0083] (1) Weigh 1 g of the electrode powder BaCo prepared in Example 1. 0.8 (Zr 1 / 6 Ti 1 / 6 Zn 1 / 6 In 1 / 6 Cu 1 / 6Mo 1 / 6 ) 0.2 O 3-δ In a high-energy ball ink tank, add 10 mL of isopropanol, 2 mL of ethylene glycol, and 0.8 mL of propylene glycol, and mill at 400 r / min for 30 min to obtain the desired electrode slurry.
[0084] (2) The prepared BZCYYb electrolyte sheet was placed on a heating table at 150°C, and the prepared electrode slurry was evenly sprayed on both sides of the electrolyte sheet by inert gas and spray gun. After the liquid was completely evaporated, the sprayed electrolyte sheet was placed in a high-temperature furnace at 1000°C and calcined for 2 hours to obtain the required symmetrical battery, which was used to test the electrode polarization impedance in the temperature range of 500-700°C. The polarization impedance of the battery measured under 5% water partial pressure conditions at 700-500°C was 0.05 and 0.47Ωcm, respectively. 2 .
[0085] Example 5
[0086] This embodiment provides a method for preparing and testing a single cell using BCZTZICM as an air electrode, and the specific steps are as follows:
[0087] (1) Weigh 1 g of the electrode powder BCZTZICM prepared in Example 1 into a high-energy ball ink tank, add 10 mL of isopropanol, 2 mL of ethylene glycol, and 0.8 mL of propylene glycol, and ball mill at 400 r / min for 30 min to obtain the desired electrode slurry.
[0088] (2) The prepared NiO-BZCYYb single cell was placed on a heating table at 150°C, and the prepared electrode slurry was evenly sprayed on the surface of the electrolyte side by an inert gas and a spray gun. After the liquid was completely evaporated, the sprayed electrolyte sheet was placed in a high-temperature furnace at 1000°C and calcined for 2 hours to obtain the required single cell, which was used to test the fuel cell performance in the temperature range of 650-500°C. The peak power density of the battery measured in the fuel cell mode at 650°C was 1.3W cm -2 Characterization results
[0089] 1. Selected Area Electron Diffraction Characterization
[0090] Figure 1 This is the selected area electron diffraction pattern of BCZTZICM, which shows a typical cubic perovskite space group structure with the [-1 1 0] crystal axis formed by the (001)(110)(111) crystal planes.
[0091] 2. Phase reaction test
[0092] Figure 2 Figure a is the XRD pattern of BCZTZICM and electrolyte BZCYYb mixed in a mass ratio of 1:1 and calcined at 1000°C for 2 hours. The XRD pattern of the mixed calcined sample does not show any new peaks compared to the XRD pattern of the original sample, indicating that no new phase is generated, and BCZTZICM and BZCYYb have good chemical compatibility. Figure 2 The b is BaCo x (Zr a Ti b Zn c In d Cu e Mo f ) y O 3-δ Rietveld refined XRD pattern of (BCZTZICM) cathode material at room temperature; the XRD pattern clearly shows that BCZTZICM powder has a cubic perovskite structure with a space group of Pm-3m, and no additional peaks appear.
[0093] 3. High-resolution transmission electron microscopy (HRTEM) characterization
[0094] Figure 3 This is a HRTEM image of BCZTZICM. The multi-element doped BCZTZICM perovskite was studied by high-resolution TEM, and lattice fringes with spacings of 0.288nm, 0.183nm, and 0.236nm were observed, corresponding to the (011), (120), and (111) crystal planes of the BCZTZICM crystal, respectively. The upper left corner is a fast Fourier transform image, and the
[211] crystal axis confirmed by the 011, 120, and 111 crystal planes.
[0095] 4. EDX-mapping element distribution diagram
[0096] Figure 4 This is the EDX-mapping element distribution diagram of BCZTZICM. EDX-mapping shows the uniformity of the overall distribution of Ba, Co, Zr, Ti, Zn, In, Cu, Mo and O elements, and the atomic ratios shown in the spectrum are close to the stoichiometric ratio.
[0097] 5. High temperature XRD characterization
[0098] Figure 5 This is the XRD spectrum of the BCZTZICM sample obtained from room temperature to high temperature; by testing the XRD spectrum of the sample at different temperatures, it can be found that its high Co content does not cause a large change in ion radius to lead to phase structure transformation at high temperature. The right figure magnifies the main peak of its 011 crystal plane, and a small leftward shift represents the lattice expansion caused by thermal reduction of Co ions.
[0099] 6. Characterization of thermal stability of phase structure
[0100] Figure 6 This is the XRD phase structure before and after calcination at 600℃ for 200 hours. There is no obvious change in the phase structure before and after calcination, and no new peaks appear, indicating that its phase structure is stable and can maintain a stable phase structure at the operating temperature.
[0101] 7. Characterization of water vapor physical adsorption capacity
[0102] Figure 7 This is the water vapor physical adsorption capacity diagram of BCZTZICM, BSCF, and BCFZY. The powders of equal mass were treated with water vapor and quenched at 250°C, and then the water vapor temperature programmed desorption (H2O-TPD) test was performed. The desorbed water vapor was detected by mass spectrometry. As can be seen from the figure, BCZTZICM has excellent water vapor physical adsorption capacity, which indicates that its microstructure as an air electrode has advantages in the kinetics of oxygen reduction reaction involving water vapor.
[0103] 8. Characterization of water vapor chemical adsorption capacity
[0104] Figure 8 This is the in-situ Fourier transform attenuated total reflection infrared spectrum of BCZTZICM, BSCF and BCFZY at high temperature. At 600℃, we tested their chemical adsorption capacity for water vapor within 45 minutes. It can be seen from the figure that BCZTZICM and BCFZY have a high adsorption capacity at 3500-3800cm -1 The characteristic peaks of BCZTZICM and BCFZY are more obvious, while the characteristic peaks of BSCF are lower in intensity. After the water vapor is removed, the characteristic peaks of BCZTZICM and BCFZY disappear quickly, indicating that water vapor has the ability to quickly adsorb and desorb on the electrode surface, while the characteristic peaks of BSCF still exist 45 minutes after the water vapor is removed, indicating that the water vapor desorption ability of BSCF is poor. During the electrolysis operation, water vapor is adsorbed on oxygen vacancies and is difficult to remove, which can easily lead to the obstruction of oxygen evolution reaction and the reduction of electrolysis performance.
[0105] 9. Characterization of hydration reaction activity
[0106] The test of the hydration reaction activity of perovskite oxides containing variable valence elements specifically includes the following specific steps:
[0107] (1) Weigh 0.5 g of the phased powders BCZTZICM, BCFZY and BSCF respectively, compact them in a press, and granulate them using a 50-mesh screen to obtain samples with uniform particle size.
[0108] (2) The sample was heated to 600°C in a tube furnace and 20% water vapor was introduced into the sample for 2 h.
[0109] (3) After processing, take out the sample quickly and cool it in air.
[0110] (4) The variable valence element content is mixed with boron nitride to prepare an X-ray absorption spectrum transmission sample.
[0111] (5) Characterize the near-edge structure of the sample to be tested by X-ray absorption spectroscopy and test the change in its valence state.
[0112] Fig. 9 ae is the X-ray absorption near-edge structure of the variable valence elements in BCZTZICM, BCFZY and BSCF. Fig. 9 After calibration with the standard sample of f, Figure 9g Summarizes the valence changes of variable valence elements in a single sample. Figure 9g BCZTZICM showed the largest valence change of 0.056, which indicates that the most proton defects were formed in BCZTZICM, indicating that it has the best hydration reaction activity, resulting in its superior proton conductivity and great advantages in proton conductor solid oxide electrolyzers.
[0113] 10. Characterization of electrolytic performance of electrolytic cell
[0114] The electrolytic cell prepared in Example 3 was used for the electrolytic current density test. Figure 10a is an electrolytic IV test of a single cell (Ni-BZCYYb|BZCYYb|BCZTZICM) prepared by BCZTZICM with Ni-BZCYYb as anode support in the range of 500-650°C. From the test results, it can be seen that the electrolytic current density of BCZTZICM at 500, 550, 600 and 650°C reaches 0.6, 0.9, 1.4 and 1.8 A cm -2 , which is higher than the 0.5, 0.7, 1.0 and 1.3 Acm obtained by the BSCF and BCFZY electrodes shown in Fig. 10 bc at the corresponding temperatures, respectively. -2 .
[0115] 11. Characterization of electrolytic cell stability
[0116] Fig.11 This is a graph of the stability of the electrolytic cell (Ni-BZCYYb|BZCYYb|BCZTZICM) prepared with BCZTZICM as the air electrode and Ni-BZCYYb as the hydrogen electrode support and tested at 550°C. -2 Under the electrolysis current of 1.5 % for 160 hours, there was no obvious trend of voltage increase. It can be seen that the BCZTZICM material maintains excellent stability, providing a guarantee for commercial progress.
[0117] 12. Thermogravimetric analysis (TGA) characterization
[0118] Fig.12 The TG curves of BCZTZICM, BSCF and BCFZY are shown in Figure 2. The mass changes of BCZTZICM, BSCF and BCFZY samples from room temperature to 1000°C in dry air are observed. BCZTZICM has the least weight loss, while BSCF has the most weight loss, indicating that its oxygen desorption is the most. According to the principle of electrical neutrality, the greater the change in the ion valence state in the structure of the corresponding material, the greater the change in the ion radius.
[0119] 13. Thermal Expansion Coefficient (TEC) Characterization
[0120] Fig.13 is the thermal expansion coefficient of BCZTZICM, BSCF and BCFZY. As a reference, the thermal expansion coefficient of the electrolyte material BZCYYb was tested to be 11.98×10 -6 K -1 , while the thermal expansion coefficient of BCZTZICM is 17.67×10 -6 K -1 The thermal expansion coefficients of BSCF and BCFZY are 22.56×10 -6 K -1 and 26.08×10 -6 K -1 BCZTZICM shows the smallest thermal expansion coefficient, indicating a better thermo-mechanical match with the electrolyte.
[0121] 14. X-ray Near Edge Structure (XANES) Characterization
[0122] Fig.14 K-edge XANES spectra of variable valence elements of BCZTZICM, BSCF, and BCFZY at room temperature and 600°C. Fig.14 a is the Co-K edge XANES spectrum of BCZTZICM. The absorption edge of Co element shows a trend of changing to lower energy level from room temperature to high temperature, which indicates that Co ions have undergone thermal reduction, resulting in an increase in coordinated electrons near the ions and the energy required to excite electrons moving to lower energy levels. Fig.14bc is the XANES spectrum of Co-K and Fe-K edges of BCFZY. Fig.14 The XANES spectra of Co-K and Fe-K edges of BSCF show the same rules as mentioned above. Fig.14 f is the change in ion valence of BCZTZICM, BCFZY, and BSCF. By comparing the change in valence from room temperature to high temperature, it can be concluded that the Co ion valence of BCZTZICM changes the least, which is 0.0752, while the ion valence of BCFZY changes to 0.117 and the ion valence of BSCF changes to 0.247, indicating that the Co ion expansion of BCZTZICM is the least, and the thermal expansion of the material caused is also the least.
[0123] 15. X-ray Photoelectron Spectroscopy (XPS) Characterization
[0124] Fig.15 XPS spectra of O1s of BCZTZICM, BSCF, and BCFZY; the O1s binding energy of BCZTZICM is 531.7 eV, while the O1s binding energy of BSCF is 531.2 eV, and the O1s binding energy of BCFZY is 531.3 eV, which indicates that the B-site multi-element doping of BCZTZICM enhances the metal-oxygen bond and inhibits the desorption of lattice oxygen, thereby achieving a lower thermal expansion coefficient.
[0125] 16. Electrochemical impedance spectroscopy
[0126] Fig.16 The Arrhenius diagram of ASR obtained on BZCYYb symmetric battery for BCZTZICM, BSCF and BCFZY under humidified air conditions in the range of 500-700℃; in the atmosphere of 5% H2O humidified air, the polarization impedance Rp of BCZTZICM in the range of 500-700℃ is 0.998, 0.354, 0.163, 0.078, 0.044Ωcm 2 , which is lower than the typical proton conductor cathode BCFZY at 500-700℃ of 1.33, 0.662, 0.337, 0.195, 0.097Ωcm 2 and 2.54, 0.881, 0.311, 0.193, 0.080Ωcm for electron and oxygen ion mixed conductors 2 . It is demonstrated that BCZTZICM has the best ORR reaction activity in proton conductor symmetric cells.
[0127] 17. Fuel cell performance test
[0128] Preparation of single cell: Ni-BZCYYb anode supported thin film electrolyte single cell was prepared by dry pressing and high temperature calcination co-pressing. First, 0.35g anode powder was pressed into a disc under 2MPa pressure, and 0.015g BZCYYb electrolyte powder was evenly distributed on the anode surface and co-pressed under 2MPa pressure. Then the obtained double-layer pellet was calcined at 1450℃ in air for 10 hours. Finally, the cathode slurry was covered on the center of the BZCYYb surface with an effective area of 0.45cm 2 , and then the three-layer battery was calcined at 1000 °C for 2 h to obtain a single cell.
[0129] Assembly of single cell: Brush silver glue on both sides of the prepared single cell electrodes, connect them with silver wires, and use silver paste to seal them on a ceramic tube with a diameter of 12 mm.
[0130] Single cell test: In hydrogen atmosphere, open circuit voltage, a current step of 10 mA is applied to the single cell, and the IV value of the battery is collected using a Keithley 2420 digital source meter.
[0131] Fig.17 The IV and IP curves of a Ni-BZCYYb|BZCYYb|BCZTZICM single cell in the fuel cell mode at 650-500°C. In the fuel cell mode, 60 mL min was introduced into the anode. -1 Hydrogen gas was introduced into the air electrode at 80 mL min -1 The peak power densities of the BCZTZICM electrode at 650, 600, 550, and 500 °C were 1.3, 0.88, 0.68, and 0.49 W cm, respectively. -2 The peak powers of BCFZY and BSCF electrodes at 650°C were only 0.92 and 0.83 W cm -2 .
[0132] 18. Single battery durability test
[0133] Fig.18 At 550℃, the BCZTZICM electrode is at 300mA cm -2 Durability test at constant current density; observe the stability of BCZTZICM single cell under operating conditions. The voltage of the single cell remains stable as a whole, and at 200h, 0.3Acm -2 It exhibits excellent durability under polarization conditions.
[0134] 19. XRD pattern of single element doped samples
[0135] Fig.19The XRD phase structure comparison of single-element doped samples and hexa-element doped BCZTZICM shows that the phase structures of the six single-element doped samples do not show a cubic phase structure with a space group of Pm-3m, and there are impure phases.
[0136] 20. XRD patterns of binary and quaternary doped samples
[0137] Fig. 20 The XRD phase structure comparison of binary and quaternary doped samples with hexavalent doped BCZTZICM shows that the phase structure of some binary and quaternary doped samples does not show a cubic phase structure with space group Pm-3m, and some of them have a hexagonal second phase with space group P63mmc.
Claims
1. A proton conductor solid oxide material, characterized in that: Its general formula is ABO 3-δ The perovskite lost material has the formula: BaCo x (Zr a Ti b Zn c In d Cu e Mo f ) y O 3-δ (BCZTZICM), where δ is the content of oxygen vacancies; and x+y=1 and a+b+c+d+e+f=1.
2. The proton conductor solid oxide material according to claim 1, characterized in that: The molecular formula is: BaCo 0.8 (Zr 1 / 6 Ti 1 / 6 Zn 1 / 6 In 1 / 6 Cu 1 / 6 Mo 1 / 6 ) 0.2 O 3-δ ; It has a cubic perovskite structure with a space group of Pm-3m and no additional peaks appear.
3. The method for preparing the proton conductor solid oxide material according to claim 1, characterized in that: It is prepared by sol-gel method according to stoichiometric ratio.
4. The preparation method according to claim 3, characterized in that: The sol-gel method comprises the following steps: firstly, tetrabutyl titanate and ammonium molybdate are heated with deionized water and monohydrated citric acid until they are clear and transparent, and then, they are prepared by the sol-gel method with barium nitrate, cobalt nitrate, zirconium nitrate, zinc nitrate, indium nitrate and copper nitrate according to the stoichiometric ratio in the molecular formula.
5. The preparation method according to claim 4, characterized in that: The sol-gel method comprises the following steps: firstly, tetrabutyl titanate and ammonium molybdate are heated and dissolved with deionized water and monohydrated citric acid until they are clear and transparent, then barium nitrate, cobalt nitrate, zinc nitrate, zirconium nitrate, copper nitrate and indium nitrate are added to dissolve and heated and stirred; ethylenediaminetetraacetic acid is added, then ammonia water is added dropwise until the pH value of the solution is between 7 and 8, and water is volatilized under heating and stirring conditions to obtain a gel-like substance; the gel-like substance is placed in an oven for drying to obtain an air electrode material precursor, and then the precursor is placed in a muffle furnace for roasting to obtain the required electrolytic cell air electrode material.
6. The preparation method according to claim 5, characterized in that: The total molar ratio of ethylenediaminetetraacetic acid and citric acid to Ba, Co, Zr, Ti, Zn, In, Cu, and Mo is 2:0.5-1.5:0.5-1.
5.
7. The preparation method according to claim 3, characterized in that: The drying process is carried out at 160-200℃ for 5-8h. The calcination parameters are 1000°C for 1-10h.
8. Use of the proton conductor solid oxide material according to claim 1 as a proton conductor in water electrolysis or in a fuel cell.
9. The use according to claim 9, characterized in that The electrolyte used is BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O3; NiO and BaZr are used as anode materials 0.1 Ce 0.7 Y 0.1 Yb 0.1 A composite anode composed of O3(BZCYYb).
10. A method for characterizing the hydration reaction activity of an air electrode of a solid oxide electrolysis cell, comprising the following steps: The air electrode material powder with the same particle size is placed in a tube furnace and treated with dry air and wet air at the operating temperature and quenched as a characterization material; Determine the ion valence of the characterization material and obtain the change in ion valence during dry air and wet air treatment; It is judged that the material with a larger change has better hydration reaction activity.
Citation Information
Patent Citations
Cathode material of solid oxide fuel cell
CN109841853A
Anode material of proton ceramic fuel cell, preparation method and application of anode material in direct ammonia fuel cell
CN116082028A
Anode material with catalytic activity
EP1432058A2
Solid-oxide fuel cell and method of manufacturing the same
JP2007287685A
Manufacturing method of solid oxide fuel cell
JP2009134980A
Cited By
A non-equimolar high-entropy proton conductor electrolyte material, its preparation method and application
CN122576270A